The Education and Jogging Physical Activities Towards Blood Sugar Levels in Patients Type 2 Diabetes Mellitus - Amirul Kadafi (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Diabetes mellitus (DM) is a disease of glucose metabolism which is characterized by an increase in blood glucose or commonly referred to as hyperglycemia caused by defects in insulin secretion, insulin work, or both. Diabetes mellitus is known as the silent killer so that diabetes mellitus is often not realized by the sufferer. Efforts to handle diabetes mellitus in a non-pharmacological way through a four-pillar approach to handling diabetes mellitus. The management of diabetes mellitus has a goal so that glucose levels in the blood remain at the limit of normal values, by referring to the four pillars of diabetes management, some of which are education and sports or physical activity. Method The type of research used is research Quasy Experimental with a pre test - post test with control group design. This study arranged three groups, namely a combination group and 2 control groups. Technique Non probability sampling with purposive sampling method was used to get 36 respondents divided into 3 groups. Results Test results Manova post hoc benferroni games howell shows p value 0.001, which means that the combination of education and physical activity of jogging is effective in significantly reducing blood sugar levels when between combination and control groups. Conclusion The results of the study after being given treatment decreased blood sugar levels when patients who received a combination of education and physical jogging activities compared to patients who were only given education or physical activity, so that the combination was effectively implemented for patients who experienced increased blood sugar levels, especially those who experienced Type 2 diabetes mellitus.